In pursuit of peace in Israel and Palestine - Baskin, Gershon (Vanderbilt University Press, 2017)
Crossing borders across the Israeli Palestinian conflict lines, Gershon Baskin provides insights and stories highlighting efforts to bridge gaps and invent solutions to the most sensitive and difficult issues in the conflict.